Building oscillations bottom up: elemental time scales of intracellular calcium dynamics - Thul, Ruediger; Falcke, Martin (World Scientific, 2007)
We analyze the elemental time scale of intracellular calcium dynamics. It is determined by the time course of Ca2+ puffs, which represent the fundamental quantum of Ca2+ release from intracellular storage compartments. Since Ca2+ puffs are truly random, we propose a novel master equation and corresponding Fokker-Planck equations. Our results demonstrate that puff initiation can be mapped to an escape process. The stochastic fraction of puff periods is identified with mean first passage times. We find that the discrete character of release sites represents a necessary condition for puff initiation. A continuous modeling of the number of open channels does not allow Ca2+ puffs in the relevant part of the parameter space.